2016
DOI: 10.1002/jsfa.7992
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization and characterization of fragrant oil from red pepper (Capsicum annuumL.) seed extracted by subcritical butane extraction

Abstract: The results indicated that the method is appropriate for the preparation of fragrant red pepper seed oil, and the oil is suitable for used as edible oil. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
4
21
0
2
Order By: Relevance
“…This phenomenon could be explained by a balance being attained between butane and oil over a period of time. Similar trends were also found in other oil extraction processes [ 15 , 26 ]. For yield and processing cost consideration, 30 min were sufficient for the extraction of seed oil.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This phenomenon could be explained by a balance being attained between butane and oil over a period of time. Similar trends were also found in other oil extraction processes [ 15 , 26 ]. For yield and processing cost consideration, 30 min were sufficient for the extraction of seed oil.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, it was concluded that 40 °C was sufficient to achieve the highest oil yield from the fenugreek seed. Similar yield trend as a function of temperature was observed in the extraction of other materials [ 26 ]. However, the highest oil yields produced from diverse material were usually achieved at different temperatures due to their distinctive biochemical composition [ 27 ].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…n‐Hexane extraction (HE) is generally considered as the best extraction method for edible oils in laboratory. The HE could be driven by the oil characteristics and induce partial alteration of minor components to effecting antioxidation and other functions . Subcritical butane extraction (SBE) has several advantages compared with traditional processing method, which is not only safe and efficient but also causes no damage to the bioactive compounds of materials .…”
Section: Introductionmentioning
confidence: 99%